The prophecy of Ulrich Beck: signposts for the social sciences - Mythen, Gabe; Burgess, Adam; Wardman, Jamie (Taylor & Francis, 2017)
This special issue on the legacy of Ulrich Beck is aimed to stimulate reflection both on the specific uses to which Beck’s conceptual and theoretical apparatus can be put within risk studies and the wider significance of his academic project for the social sciences. In this end-piece, we draw out the key themes which surface in the different contributions relating to five particular areas: the nature of risk; advancements in methods; issues of non-knowledge and uncertainty; the development of cosmopolitan risk communities; and the situated character of individualization. We discuss the implications of the accounts contained in this special issue and reflect on the impact and influence of Beck’s sustained engagement with colleagues around the globe, concluding that the concepts and methods that Beck bequeathed the social sciences are set to live on and thrive.